DNA-damaging agents greatly increase the transduction of nondividing cells by adeno-associated virus vectors. - Alexander, I E (1994)
None of the vector systems currently available for gene therapy applications have been shown to be capable of both efficient gene transfer into nondividing cells and long-term expression through stable integration into host cell DNA. While integrating vectors based on adeno-associated virus are capable of mediating gene transfer into nondividing cells, this process is 200-fold less efficient than transduction of dividing cells. We demonstrate that the transduction efficiency of adeno-associated virus vectors can be increased by treatment with DNA-damaging agents. Nondividing cells are especially responsive, with increases in transduction efficiency of up to 750-fold. This finding has the potential to facilitate gene therapy applications requiring gene transfer to nondividing cells.